Flat ceilings in historic buildings. - Nicer, Tomasz (Budownictwo i Architektura / Civil and Architectural Engineering, 2009)
Every building type action on a historic object should include recognition of character, age and the technology of constructional solutions. The conservator’s preservation can concern, and in some cases should concern the structural solutions. Such analysis are particularly difficult in the case of flat ceilings. Possibilities of historic as well as contemporary solutions of the structure, their origins, similarity in assumptions and materials and the ignorance of the historical technologies can lead to wrong conclusions. Conclusions can be wrong both in relation to the originality and the authenticity of solutions, and can lead to undesirable workings from the conservatory point of the view in the consequence.